Propuesta de creación de una cooperativa de ahorro y crédito agropecuaria “juntos somos más”, como una alternativa de desarrollo económico para la parroquia Guasaganda del cantón La Maná Año 2012. - Velásquez Reyes Estefanía Del Pilar. (2015)
For this research proposal is seen as creating a Savings and Credit Cooperative Agriculture, "Together We Are More" as an alternative economic development for the Parish of Canton La Maná Guasaganda for 2012, to provide credit services according to population development. Parish Guasaganda is a predominantly agricultural and livestock, most economically active population is engaged in farming activities. In the area are mainly grown: Bananas, baby bananas, cassava, maize and a large area for cattle pasture. In regard to cattle raising livestock is the main source of income in the economy of families in the parish and in small proportion raised sheep, pigs and poultry. The credit union credit services provide short and medium term with amounts up to $ 3000 for the first year of operation, capturing savings through incentives that create a culture of savings, transfer services with respect to deposits and withdrawals of money according to the needs of its members, which will offer ongoing training regarding cooperative production and other aspects that requires the parish....